1994
DOI: 10.1111/j.1365-2133.1994.tb03382.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of calcipotriol (MC903) solution and placebo (vehicle of MC903) in the treatment of psoriasis of the scalp

Abstract: The efficacy and safety of calcipotriol solution in the treatment of scalp psoriasis was compared with placebo (vehicle solution), in a multicentre double-blind, randomized, parallel-group study of 49 adult patients. Calcipotriol solution (50 micrograms/ml), or placebo, was applied twice daily over a 4-week period. At the end of the study period 60% of patients on calcipotriol showed clearance or marked improvement of their psoriasis compared with 17% on placebo. Overall assessment of treatment response showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 9 publications
0
48
0
1
Order By: Relevance
“…In the treatment of scalp psoriasis, calcipotriol solution has been shown to be safe and effective for both short-term and long-term treatments [13,14,15]. The primary benefit of calcipotriol in the treatment of scalp psoriasis is the strong safety profile related to repeated use, allowing long-term treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of scalp psoriasis, calcipotriol solution has been shown to be safe and effective for both short-term and long-term treatments [13,14,15]. The primary benefit of calcipotriol in the treatment of scalp psoriasis is the strong safety profile related to repeated use, allowing long-term treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A placebo-controlled comparison of calcipotriol solution confirmed that calcipotriol significantly reduces the symptoms of scalp psoriasis after 4 weeks of treatment, according to both investigator and patient assessments (P < 0.001 for both). 16 More recently, in a large prospective, observational study (n ¼ 3396) of scalp psoriasis patients treated with calcipotriol solution for 8 weeks, 80% of patients showed 'good' or 'very good' clinical improvement. 20 However, as noted above, in two comparisons with betamethasone valerate (solution, n ¼ 474; and lotion, n ¼ 42), the corticosteroid proved more efficacious.…”
mentioning
confidence: 99%
“…Currently available synthetic vitamin D 3 analogues include calcipotriol, maxacalcitol, tacalcitol and calcitriol. There are only small open studies that show that calcipotriene's optimal effect occurs at 8 weeks and lasts 52 weeks [9,23]. These agents are only minimally systemically absorbed and therefore have few systemic side effects.…”
Section: Discussionmentioning
confidence: 99%